Son - Lowry, Lois. (Boston, Mass. : Houghton Mifflin Harcourt, 2012)
Unlike the other Birthmothers in her utopian community, teenaged Claire forms an attachment to her baby, feeling a great loss when he is taken to the Nurturing Center to be adopted by a family unit.
Companion book to: The Giver, Gathering blue, and Messenger.
Keywords: Science fiction; Mother and child -- Fiction; Separation (Psychology) -- Fiction